Motivasi Pemilihan Lintas Minat Sains pada Siswa Jurusan Ilmu Sosial - Yendrita Yendrita (SPEJ (Science and Physic Education Journal), 2019)
This study aims to find out how intrinsic and extrinsic motivation affects students of the Social Sciences Department of SMA N I Suliki District in choosing cross-interest of Science. This type of research is quantitative research with descriptive methods. The research instrument is a set of questionnaire. Samples were taken with a total sampling technique, then the subjects of this study were all students of class X majoring in Social Sciences who chose cross interest of Science, amounting to 126 people, data analysis technique is a percentage technique. Based on the results of data analysis, intrinsic motivation that influences the selection of cross-student interests is as follows: based on ideals of 70.58%, based on student abilities of 69.44%, based on student conditions of 70.33%, based on interests of 66.93 %, based on the attitude of 75.06%, while extrinsic motivation that influences the selection of students' cross-interest is as follows; based on family encouragement of 62.56%, encouragement of friends 59.32%, employment opportunities of 69.57% and opportunities to continue study 61.50%. Whereas based on sub-variables, intrinsic motivation was found to influence the cross-selection of scientific interest by 70.48% (in the good category) and extrinsic motivation by 62.75% (in the good category). The conclusions of this study are: intrinsic motivation influences students more in crossing scientific interests than extrinsic motivation Keywords: Motivation, SAINS Cross-Interest Selection,